Negative pole piece, solid-state battery and activation method
By using a combination of composite current collector and silicon negative electrode coating in the negative electrode sheet of solid state battery, the problem of excessive stress during the deintercalation of lithium in the silicon negative electrode sheet is solved, and the electrochemical performance and stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202411549905.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-18
AI Technical Summary
The existing silicon negative electrode sheets generate huge stress during the deintercalation of lithium, resulting in degradation of electrochemical performance and battery failure.
The composite fluid collector is used as the basis of the negative electrode sheet, including a metal layer and an elastomeric layer, and the silicon negative electrode coating is arranged on at least one side of the composite fluid collector to reduce stress and improve battery performance.
During the deintercalation process of lithium, reduce stress, stabilize activation capacity, reduce electrical performance attenuation, and improve the overall performance of solid-state batteries.
Smart Images

Figure BDA0005114792230000091 
Figure BDA0005114792230000101 
Figure BDA0005114792230000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular, to a negative electrode sheet, and more particularly, to a solid-state battery, an activation method, and an electronic device. Background Art
[0002] Silicon negative electrode materials have the advantages of high specific capacity, abundant resources, and good processing performance. They have good application prospects in high specific energy lithium-ion batteries, especially solid-state batteries. Since solid-state batteries do not contain flammable liquid organic electrolytes, their safety is considered to be higher than that of current liquid lithium-ion batteries, making them a current research hotspot. However, existing silicon negative electrode plates will produce huge stress, resulting in a serious decline in the electrochemical performance of the silicon negative electrode, causing battery failure.
[0003] Therefore, it is urgent to develop new negative electrode plates to reduce the huge stress generated by the negative electrode plates and improve battery performance. Summary of the invention
[0004] In the first aspect of the present application, the present application proposes a negative electrode plate. According to an embodiment of the present application, the negative electrode plate includes: a composite current collector; a silicon negative electrode coating, and the silicon negative electrode coating is arranged on at least one side of the composite current collector; wherein the composite current collector includes a metal layer and an elastomer layer, and the metal layer is arranged on both sides of the elastomer layer. According to the negative electrode plate of the embodiment of the present application, the stress generated during the lithium insertion and extraction process is reduced, the capacity of the activation process is more stable, and the attenuation is less, which has a positive effect on improving the performance of the solid-state battery.
[0005] In a second aspect of the present application, the present application proposes a solid-state battery. According to an embodiment of the present application, the solid-state battery comprises the negative electrode sheet, the positive electrode sheet and the solid electrolyte layer described in the first aspect of the present application. According to the solid-state battery of the embodiment of the present application, the battery performance is improved.
[0006] In the third aspect of the present application, the present application proposes an activation method. According to an embodiment of the present application, the method includes placing the solid-state battery described in the second aspect of the present application in a constant pressure fixture to charge and discharge the solid-state battery for activation. The method according to the embodiment of the present application can improve the battery performance of the solid-state battery.
[0007] In a fourth aspect of the present application, the present application provides an electronic device. According to an embodiment of the present application, the electronic device includes the solid-state battery described in the second aspect of the present application. According to the electronic device of the embodiment of the present application, the electrical performance is improved.
[0008] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0010] Figure 1 This is a negative electrode plate in Example 1.
[0011] Figure 2 This is a solid-state battery in Example 1.
[0012] Figure 3 Schematic diagram of the device for activating the solid-state battery in Example 1.
[0013] Figure numerals: metal layer 11 of composite current collector; elastomer layer 12 of composite current collector; silicon negative electrode coating 13; pressure sensor 31 of constant pressure tooling; pressure plate 32; solid-state battery 33; charge-discharge and constant pressure control system 34. DETAILED DESCRIPTION
[0014] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0015] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0016] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0017] In the description of the present application, it should be understood that the terms "width", "thickness", etc. indicate orientation or positional relationships based on the orientation or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0018] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.
[0019] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0020] In the description of the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0021] In the description of the present application, “plurality” means two or more.
[0022] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0023] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0024] The volume expansion of the silicon negative electrode during the lithium extraction process generates huge stress, the electrode forms cracks or even shatters, the contact between the electrode and the current collector deteriorates, the resistance increases and the active material is lost, resulting in a serious decline in the electrochemical performance of the silicon negative electrode and battery failure. During the activation or testing process of solid-state batteries, a fixed metal clamp is usually required to apply a large external pressure in order to charge and discharge normally. However, as the battery expands and contracts, the metal clamp cannot maintain the pressure on the battery, and the stress inside the battery, especially the silicon negative electrode, cannot be constrained and released, and the electrical performance decays faster. In order to overcome these problems, the inventors have developed a new negative electrode to reduce the huge stress caused by the volume expansion of the silicon negative electrode during the lithium extraction process, thereby improving the electrical performance of solid-state batteries.
[0025] Based on this, in the first aspect of the present application, the present application proposes a negative electrode plate. According to an embodiment of the present application, the negative electrode plate includes: a composite current collector; a silicon negative electrode coating, and the silicon negative electrode coating is arranged on at least one side of the composite current collector; wherein the composite current collector includes a metal layer and an elastomer layer, and the metal layer is arranged on both sides of the elastomer layer. According to the negative electrode plate of the embodiment of the present application, the stress generated during the lithium insertion and extraction process is reduced, the capacity of the activation process is more stable, and the attenuation is less, which has a positive effect on improving the performance of the solid-state battery.
[0026] In some embodiments, the negative electrode plate is composed of a silicon negative electrode slurry coated on a composite current collector containing an elastomer.
[0027] In some embodiments, the silicon negative electrode slurry includes a silicon negative electrode, a binder, and a conductive agent, and a solid electrolyte may be added or not. The silicon negative electrode includes but is not limited to one or more of silicon, silicon oxide, and silicon carbon; the binder includes but is not limited to polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyacrylate, sodium alginate, chitosan, etc.; the conductive agent includes but is not limited to one or more of conductive carbon black, carbon nanotubes, acetylene black, and graphene; the solid electrolyte includes but is not limited to one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, sulfide, and halide.
[0028] In some embodiments, the metal layer includes copper foil.
[0029] In some embodiments, the elastomeric layer includes at least one of polyethylene, polypropylene, polyimide, polyethylene oxide, polyethylene terephthalate, silicone rubber, rubber, styrene-butadiene-styrene block copolymer, styrene-isoprene block copolymer rubber, ethylene propylene diene rubber, polyolefin thermoplastic elastomer and thermoplastic polyurethane.
[0030] In some embodiments, the elastomeric layer includes at least one of polypropylene, polyethylene oxide, polyethylene terephthalate, and silicone rubber.
[0031] In some embodiments, the silicon anode coating includes at least one of silicon, silicon monoxide, and silicon carbon.
[0032] In some embodiments, the thickness of the silicon negative electrode coating is 40-100 μm, for example, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or a range of 45-100 μm, 50-100 μm.
[0033] In some embodiments, the thickness of the metal layer is 1 to 10 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range of 2 to 10 μm, 3 to 10 μm therebetween, and the thickness of the elastomer layer is 2 to 100 μm, for example, it can be 2 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or a range of 5 to 100 μm, 10 to 100 μm therebetween.
[0034] In some embodiments, the thickness of the metal layer is 1 to 8 μm, and the thickness of the elastomer layer is 10 to 90 μm.
[0035] In some embodiments, the thickness of the metal layer is 1 to 5 μm, and the thickness of the elastomer layer is 10 to 90 μm.
[0036] In some embodiments, the thickness of the elastomeric layer satisfies the formula: dE*m≥k*dCL*n; wherein dE is the thickness of the elastomeric layer, m is the compressibility of the elastomeric layer, dCL is the thickness of the negative electrode coating, n is the expansion rate of the negative electrode coating from the delithiation state to the lithium insertion state, and k is the expansion absorption coefficient, preferably 0.1 to 1.
[0037] In the second aspect of the present application, the present application proposes a solid-state battery. According to an embodiment of the present application, the solid-state battery includes the negative electrode sheet, the positive electrode sheet and the solid electrolyte layer described in the first aspect of the present application. According to the embodiment of the present application, it should be explained that the "solid-state battery" includes all-solid-state batteries and batteries containing a certain proportion of liquid electrolytes, such as semi-solid-state batteries and quasi-solid-state batteries. Specifically, all-solid-state batteries do not contain any liquid electrolytes, and all electrolytes are solid. Such batteries are generally safer because solid electrolytes are non-flammable and can inhibit the growth of lithium dendrites, thereby reducing the risk of short circuits. In addition, the energy density of all-solid-state batteries is generally higher because metallic lithium can be used as the negative electrode material to achieve a higher energy density. All-solid-state batteries have a long cycle life, a wide temperature range, and better mechanical strength and stability. Semi-solid-state batteries contain a small amount of liquid electrolyte, and the mass percentage of liquid electrolyte is generally around 5-10%. Semi-solid-state batteries improve safety while maintaining a certain high ion transfer rate of liquid batteries. They are a transitional technology between traditional liquid lithium batteries and all-solid-state batteries. Quasi-solid-state batteries refer to batteries with a liquid electrolyte mass percentage of less than 5%. Such batteries have a higher solid electrolyte content and less liquid electrolyte, and are safer than semi-solid-state batteries, but still not as safe as all-solid-state batteries. According to the solid-state battery of the embodiment of the present application, the battery performance is improved.
[0038] In some embodiments, the positive electrode plate is composed of a positive electrode material, a conductive agent, and a binder, and a solid electrolyte may be added or not, mixed into a slurry and then coated on the surface of the positive electrode current collector. The positive electrode material includes but is not limited to one or more of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium cobalt oxide, lithium nickel oxide, and lithium-rich manganese-based positive electrode; the binder includes but is not limited to polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyacrylate, sodium alginate, chitosan, etc.; the conductive agent includes but is not limited to one or more of conductive carbon black, carbon nanotubes, acetylene black, and graphene; the solid electrolyte includes but is not limited to one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, sulfide, and halide. According to an embodiment of the present application, the positive electrode current collector is an aluminum foil with a thickness of 4 to 30 μm, for example, 4 μm, 6 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm or a range of 6 to 30 μm, 8 to 30 μm.
[0039] In the third aspect of the present application, the present application proposes an activation method. According to an embodiment of the present application, the method includes placing the solid-state battery described in the second aspect of the present application in a constant pressure fixture to charge and discharge the solid-state battery for activation. The method according to the embodiment of the present application can improve the battery performance of the solid-state battery.
[0040] In some embodiments, the charging and discharging activation of the solid-state battery is performed in the following manner: an initial pressure value is set, and a pressure sensor is provided in the constant pressure tooling to ensure that the reading of the pressure sensor during the activation process is the same as the set initial pressure value.
[0041] In some embodiments, the initial pressure value is 0.5MPa~300MPa, for example, it can be 0.5MPa, 1MPa, 5MPa, 10MPa, 20MPa, 50MPa, 80MPa, 100MPa, 150MPa, 200MPa, 250MPa, 300MPa or a range between 1MPa~300MPa, 5MPa~300MPa.
[0042] In some embodiments, the initial pressure value is 1 MPa to 100 MPa.
[0043] In a fourth aspect of the present application, the present application provides an electronic device. According to an embodiment of the present application, the electronic device includes the solid-state battery described in the second aspect of the present application.
[0044] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0045] Embodiment 1:
[0046] (1) The positive electrode material listed in this embodiment is lithium nickel cobalt manganese oxide, and the negative electrode material is silicon negative electrode.
[0047] (2) Lithium nickel cobalt manganese oxide is mixed with polyvinylidene fluoride (PVDF), conductive carbon black, and carbon nanotubes in a ratio of 95:2:2:1, and subjected to a coating and rolling process, and coated on a positive electrode current collector (aluminum foil) to prepare a positive electrode sheet of a lithium battery.
[0048] (3) The silicon negative electrode is mixed with sodium carboxymethyl cellulose (CMC) glue, styrene-butadiene rubber (SBR) emulsion, conductive carbon black, and carbon nanotubes in a ratio of 93:2:3:1:1, and subjected to coating and rolling processes, and coated on the negative electrode current collector (the thickness of the current collector is 8 μm, the metal layer of the current collector is copper foil, the thickness of the metal layer is 1 μm; the elastomer layer is polyethylene oxide, and the thickness of the elastomer layer is 6 μm) to prepare a negative electrode sheet of a lithium battery, and the thickness of the negative electrode coating is 50 μm.
[0049] (4) The sulfide solid electrolyte slurry is coated on the surface of the positive electrode material after rolling, with a thickness of 100 μm.
[0050] (5) The above-mentioned negative electrode sheet and the positive electrode sheet in Example (4) are cut and stacked, the tabs are welded, and the sheets are sealed with an aluminum-plastic film to prepare a lithium-ion battery cell.
[0051] (6) The above battery cell is subjected to isostatic pressing at a pressure of 300 MPa.
[0052] (7) Place the above isostatically pressed battery cell into a constant pressure tooling, set the initial pressure value; connect the charge and discharge channels to activate the above battery cell. The activation steps used are: 0.01C constant current charging for 10 hours, 0.05C constant current charging to 4.2V, switching to constant voltage charging until the current drops to 0.02C, standing for 1 hour, discharging at 0.1C constant current to 2.5V; charging at 0.1C constant current to 4.2V, switching to constant voltage charging until the current drops to 0.02C, standing for 1 hour, discharging at 0.1C constant current to 2.5V, and repeating 5 times.
[0053] (8) Record the thickness and capacity of the activated battery cell.
[0054] Embodiment 2:
[0055] The experimental process of this embodiment is basically the same as that of embodiment 1, except that the thickness of the current collector is 26 μm, the thickness of the elastomer layer is 20 μm, the thickness of the metal layer is 3 μm, and the other contents are the same as those of embodiment 1.
[0056] Embodiment 3:
[0057] The experimental process of this embodiment is basically the same as that of embodiment 1, except that the thickness of the current collector is 56 μm, the thickness of the elastomer layer is 50 μm, the thickness of the metal layer is 3 μm, and the other contents are the same as those of embodiment 1.
[0058] Embodiment 4:
[0059] The experimental process of this embodiment is basically the same as that of Embodiment 1, except that the thickness of the current collector is 56 μm, the thickness of the elastomer layer is 50 μm, the thickness of the metal layer is 3 μm, the elastomer layer is silicone rubber, and other contents are the same as those of Embodiment 1.
[0060] Embodiment 5:
[0061] The experimental process of this embodiment is basically the same as that of Embodiment 1, except that the thickness of the current collector is 56 μm, the thickness of the elastomer layer is 50 μm, the thickness of the metal layer is 3 μm, the elastomer layer is polyethylene terephthalate, and the other contents are the same as those of Embodiment 1.
[0062] Embodiment 6:
[0063] The experimental process of this embodiment is basically the same as that of embodiment 1, except that the elastomer layer is polypropylene, and the other contents are the same as those of embodiment 1.
[0064] Embodiment 7:
[0065] The experimental process of this embodiment is basically the same as that of Embodiment 1, except that the thickness of the current collector is 26 μm, the thickness of the elastomer layer is 20 μm, the thickness of the metal layer is 3 μm, the elastomer layer is polypropylene, and the other contents are the same as those of Embodiment 1.
[0066] Embodiment 8:
[0067] The experimental process of this embodiment is basically the same as that of Embodiment 1, except that the thickness of the current collector is 56 μm, the thickness of the elastomer layer is 50 μm, the thickness of the metal layer is 3 μm, the elastomer layer is polypropylene, and the other contents are the same as those of Embodiment 1.
[0068] Embodiment 9:
[0069] The experimental process of this embodiment is basically the same as that of Embodiment 1, except that the thickness of the current collector is 56 μm, the thickness of the elastomer layer is 50 μm, the thickness of the metal layer is 3 μm, the elastomer layer is polypropylene, the thickness of the negative electrode coating is 80 μm, and the other contents are the same as those of Embodiment 1.
[0070] Embodiment 10:
[0071] The experimental process of this embodiment is basically the same as that of Embodiment 1, except that the thickness of the current collector is 56 μm, the thickness of the elastomer layer is 50 μm, the thickness of the metal layer is 3 μm, the elastomer layer is polypropylene, the thickness of the negative electrode coating is 100 μm, and the other contents are the same as those of Embodiment 1.
[0072] Embodiment 11:
[0073] The experimental process of this embodiment is basically the same as that of Embodiment 1, except that the thickness of the current collector is 80 μm, the thickness of the elastomer layer is 70 μm, the thickness of the metal layer is 5 μm, the elastomer layer is polypropylene, the thickness of the negative electrode coating is 100 μm, and the other contents are the same as those of Embodiment 1.
[0074] Embodiment 12:
[0075] The experimental process of this embodiment is basically the same as that of Embodiment 1, except that the thickness of the current collector is 100 μm, the thickness of the elastomer layer is 90 μm, the thickness of the metal layer is 5 μm, the elastomer layer is polypropylene, the thickness of the negative electrode coating is 100 μm, and the other contents are the same as those of Embodiment 1.
[0076] Embodiment 13:
[0077] The experimental process of this embodiment is basically the same as that of embodiment 1, except that the elastic layer is silicone rubber, and the other contents are the same as those of embodiment 1.
[0078] Embodiment 14:
[0079] The experimental process of this embodiment is basically the same as that of embodiment 1, except that the elastic layer is polyethylene terephthalate, and the other contents are the same as those of embodiment 1.
[0080] Embodiment 15:
[0081] The experimental process of this embodiment is basically the same as that of embodiment 1, except that the thickness of the negative electrode coating is 80 μm. Other contents are the same as those of embodiment 1.
[0082] Embodiment 16:
[0083] The experimental process of this embodiment is basically the same as that of embodiment 1, except that the thickness of the negative electrode coating is 100 μm, and the other contents are the same as those of embodiment 1.
[0084] Comparative Example 1:
[0085] The experimental process of this comparative example is basically the same as that of Example 1, except that no elastic layer is provided on the negative electrode current collector, and other contents are the same as those of Example 1.
[0086] Comparative Example 2:
[0087] The experimental process of this comparative example is basically the same as that of Example 1, except that no elastic layer is provided on the negative electrode current collector, the activation pressurization method is a metal clamp, and the other contents are the same as those of Example 1.
[0088] Comparative Example 3:
[0089] The experimental process of this comparative example is basically the same as that of Example 1, except that the activation pressurization method is a metal clamp, and the other contents are the same as those of Example 1.
[0090] Comparative Example 4:
[0091] The experimental process of this comparative example is basically the same as that of Example 2, except that the activation pressurization method is a metal clamp, and the other contents are the same as those of Example 2.
[0092] Comparative Example 5:
[0093] The experimental process of this comparative example is basically the same as that of Example 3, except that the activation pressurization method is a metal clamp, and the other contents are the same as those of Example 3.
[0094] Comparative Example 6:
[0095] The experimental process of this comparative example is basically the same as that of Example 4, except that the activation pressurization method is a metal clamp, and the other contents are the same as those of Example 4.
[0096] Comparative Example 7:
[0097] The experimental process of this comparative example is basically the same as that of Example 5, except that the activation pressurization method is a metal clamp, and the other contents are the same as those of Example 5.
[0098] Comparative Example 8:
[0099] The experimental process of this comparative example 3 is basically the same, except that the activation and pressurization method is a metal clamp, the elastomer layer is polypropylene, and the other contents are the same as Example 3.
[0100] Table 1: Cell information and activation results of Examples and Comparative Examples
[0101]
[0102]
[0103]
[0104] Comparison between Example 1 and Comparative Example 1 shows that the activation capacity retention rate of the battery cell prepared by disposing an elastomer layer on the negative electrode current collector is higher than that of the battery cell prepared by not disposing an elastomer layer.
[0105] Comparison between Example 1 and Comparative Example 2 shows that the activation capacity retention rate of the battery cell in which an elastic layer is arranged on the negative electrode current collector and the activation pressurization method is prepared by a constant pressure tool is improved compared with the battery cell in which no elastic layer is arranged and the activation pressurization method is prepared by a metal fixture.
[0106] From the comparison between Example 1 and Comparative Example 3, Example 2 and Comparative Example 4, Example 3 and Comparative Examples 5 and 8, Example 4 and Comparative Example 6, and Example 5 and Comparative Example 7, it can be seen that the battery cells prepared by using the constant pressure tooling as the activation pressurization method for the negative electrode current collector have a higher activation capacity retention rate than the battery cells prepared by using the metal fixture as the activation pressurization method.
[0107] Comparison between Example 1 and Examples 2 and 3 shows that the activation capacity retention rate of the battery cell prepared with thicker current collector, metal layer and elastomer layer is higher than that of the battery cell prepared with thinner current collector, metal layer and elastomer layer.
[0108] Comparison of Example 1 with Examples 6, 13, and 14 shows that the activation capacity retention rate of the battery cell whose elastomer layer is made of polyethylene oxide is higher than that of the battery cell whose elastomer layer is made of silicone rubber or polyethylene terephthalate.
[0109] Comparison between Example 1 and Examples 15 and 16 shows that the activation capacity retention rate of the battery cell prepared with a thinner negative electrode coating is higher than that of the battery cell prepared with a thicker negative electrode coating.
[0110] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0111] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A negative electrode plate, characterized in that: include: Composite current collector; A silicon negative electrode coating, wherein the silicon negative electrode coating is disposed on at least one side of the composite current collector; Wherein, the composite current collector comprises a metal layer and an elastomer layer, and the metal layer is arranged on both sides of the elastomer layer.
2. The negative electrode sheet according to claim 1, characterized in that: The metal layer includes copper foil.
3. The negative electrode sheet according to claim 1, characterized in that: The elastomer layer includes at least one of polyethylene, polypropylene, polyimide, polyethylene oxide, polyethylene terephthalate, silicone rubber, rubber, styrene-butadiene-styrene block copolymer, styrene-isoprene block copolymer rubber, ethylene propylene diene rubber, polyolefin thermoplastic elastomer and thermoplastic polyurethane.
4. The negative electrode sheet according to claim 1, characterized in that: The elastomer layer includes at least one of polypropylene, polyethylene oxide, polyethylene terephthalate, and silicone rubber.
5. The negative electrode sheet according to claim 1, characterized in that: The silicon negative electrode coating includes at least one of silicon, silicon monoxide and silicon carbon.
6. The negative electrode sheet according to claim 1, characterized in that: The thickness of the silicon negative electrode coating is 40-100 μm.
7. The negative electrode sheet according to claim 1, characterized in that: The thickness of the metal layer is 1 to 10 μm, and the thickness of the elastic layer is 2 to 100 μm.
8. The negative electrode sheet according to claim 1, characterized in that: The thickness of the metal layer is 1 to 8 μm, and the thickness of the elastic layer is 10 to 90 μm.
9. The negative electrode sheet according to claim 1, characterized in that: The thickness of the elastomer layer satisfies the formula: d E *m≥k*d CL *n; wherein, dE is the thickness of the elastomer layer, m is the compressibility of the elastomer layer, dCL is the thickness of the negative electrode coating, n is the expansion rate of the negative electrode coating from the delithiation state to the lithium insertion state, and k is the expansion absorption coefficient, preferably 0.1 to 1.
10. A solid-state battery, characterized in that: include: The negative electrode sheet, positive electrode sheet and solid electrolyte layer as claimed in any one of claims 1 to 9.
11. An activation method, characterized in that: The solid-state battery according to claim 10 is placed in a constant pressure tooling to perform charge and discharge activation on the solid-state battery.
12. The activation method according to claim 11, characterized in that: The charging and discharging activation of the solid-state battery is performed in the following manner: an initial pressure value is set, a pressure sensor is provided in the constant pressure tooling, and the reading of the pressure sensor during the activation process is ensured to be the same as the set initial pressure value.
13. The activation method according to claim 12, characterized in that: The initial pressure value is 0.5MPa to 300MPa.
14. The activation method according to claim 12, characterized in that: The initial pressure value is 1 MPa to 100 MPa.
15. An electronic device, characterized in that: include: The solid-state battery according to claim 10.
Citation Information
Patent Citations
Anode for high-energy batteries
CN112038578A
Tab-free cylindrical battery and preparation method thereof
CN112928281A
Negative plate and application thereof
CN113066954A
Negative pole piece, secondary battery and device thereof
CN117276462A
Silicon / silver carbon composite negative electrode, preparation method thereof and all-solid-state battery
CN118572037A